ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN PSAK 73: STUDI PADA PT SEMEN INDONESIA (PERSERO) TBK. PERIODE 2018-2022 - Rosyidah, Alim Matur; Dwi Suhartini (Politeknik Keuangan Negara STAN, 2025)
This study aims to assess the impact of the implementation of PSAK 73 on the financial performance of PT Semen Indonesia (Persero) Tbk., particularly on profitability and solvency ratios. Data were obtained from the company's annual financial reports for the period 2018–2022, accessed through the official website of PT Semen Indonesia (Persero) Tbk. The analysis was conducted using a qualitative descriptive method by comparing financial ratios before and after the implementation of PSAK 73, and presenting the results in tables and graphs. The results of the analysis show a decline in profitability with ROA falling from 4.53% to 2.98% and ROE from 8.64% to 6.34%. Conversely, solvency improved with DAR decreasing from 28.28% to 26.06% and DER from 61.94% to 55.78%. The implementation of PSAK 73 also increased total assets by 2.51%, but did not have a significant effect on financial performance. These findings provide input for management to review financial strategies in adjusting to new accounting standards